The Olive Polyphenol Hydroxytyrosol Enhances Autophagy and Heme Oxygenase-1 Expression in Aortic Endothelial Cells and Reduces Arterial Stiffness ex vivo - Lauwers, Stef; Van Praet, Melissa; Steenput, Bieke; Weyns, Anne-Sophie; Neutel, Cédric H.G.; Tuenter, Emmy; Hermans, Nina; Roth, Lynn (Planta Medica, 2025)
Age-related arterial stiffening is a hallmark of vascular ageing and a key driver of cardiovascular disease. Oxidative stress, impaired autophagy, and extracellular matrix remodelling play an important role in the progression of aortic stiffening. Hydroxytyrosol (HT), a phenolic compound in olives, has demonstrated antioxidant properties and the ability to modulate autophagy, positioning it as a potential therapeutic for vascular ageing. In this study, we investigated the effects of HT on autophagy flux and antioxidant protein expression in human aortic endothelial cells (HAoECs). In parallel, we examined the impact of HT on arterial stiffness ex vivo using isolated aortic segments from wild-type (WT) and Fbn1C1039G+/- mice, a model of elastin fragmentation.HT treatment (50 and 100 µM; 18 h) enhanced autophagy flux in HAoECs, evidenced by increased LC3-II and p62 turnover, and reduced mTOR activity. Additionally, HT upregulated heme oxygenase-1 (HO-1), a key antioxidant enzyme. Ex vivo treatment of aortic segments from WT and Fbn1C1039G+/- mice with HT (50 µM; 18 h) restored IP3-mediated contractions and reduced aortic stiffness in Fbn1C1039G+/- aortas, as demonstrated by a decreased Petersonʼs modulus. Although HT did not significantly affect collagen or elastin content or elastic fibre breaks in the aortic wall, it notably increased HO-1 protein levels in Fbn1C1039G+/- aortas.These findings demonstrate the potential of HT to mitigate oxidative stress, enhance autophagy, and reduce arterial stiffness, making it a promising nutraceutical for addressing age-related vascular dysfunction. Further long-term studies are needed to elucidate the molecular mechanisms and evaluate its sustained benefits in vivo.
Keywords: arterial stiffness; elastin; autophagy; heme oxygenase-1; oxidative stress; vascular ageing; Olea europaea; Oleaceae